Health outcomes and psychosocial risk exposures among healthcare workers during the first wave of the COVID-19 outbreak. (January 2022) - Moreno Martínez, Marina; Fernández-Cano, María Isabel; Feijoo-Cid, Maria; Llorens Serrano, Clara; Navarro, Albert
Highlights: Health Care Workers had poorer health and more job demands than the general population. Women and frontline Health Care Workers had more exposure to psychosocial risks. Geriatric assistants were the most-affected occupational group. Abstract: Introduction: The aim is to describe the health and psychosocial risk factors of Spanish healthcare workers during the COVID-19 pandemic. Methods: A cross-sectional study by means of an online questionnaire (April–May 2020). The data comes from the database resulting from the COTS project "Working conditions, insecurity, and health in the context of the COVID-19 pandemic". The sample consisted of 1989 health care workers. Results: Women, young people (doctors and nurses) and the middle-aged (assistants) had poorer health and greater exposure to psychosocial risks. Geriatric assistants were the most-affected occupational group. Conclusions: gender, occupation, and age are focuses of inequality in the exposure of health care workers to psychosocial risks.